Mechanochemical synthesis of barium titanate - Stojanovic, B. D.; Simoes, A. Z.; Paiva-Santos, C. O.; Jovalekic, C.; Mitic, V. V.; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
A powder mixture of BaO and TiO2, was mechanochemically treated in a planetary ball mill in an air atmosphere for up to 4 h, using zirconium oxide vial and zirconium oxide balls as the milling medium. Mechanochemical reaction leads to the gradual formation of BaTiO3 phase. Phase evolution during synthesis and changes in powder size and morphology were monitored by XRD, DSC, IR and TEM analysis and it was shown that the formation of BaTiO3 phase was initiated after 60 min. Extended time of milling directed to formation of higher amount of BaTiO3 perovskite phase. Barium titanate with good crystallinity was formed after 240 min sintering without pre-calcination step was performed at 1330 degrees C for 2 It within heating rate 10 degrees C/min. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: barium titanate